The reception of English fictional and non-fictional prose in Catalonia (1916-38), with particular reference to Edwardian literary culture and associated debates concerning the novel in England, France and Catalonia - Coll-Vinent, S; Coll-Vinent, Silvia (1996)
﻿ The present study opens up the field of Catalan connections with English literature. The importance of Edwardian influences on the general transmission of English authors and works is demonstrated. Original data on the reception of G.K. Chesterton, the Edwardian figure with a most remarkable impact in Catalonia, is brought to light (Chapter 1, Appendix 1), followed by discussion of the presence of H.G. Wells and G.B. Shaw and an account of the reception of Well's early fiction (Chapter 2); their influence sheds new light on the aspiration of an élite to modernise Catalan culture. Catalan translations of English fictional works produced in the period 1918-38 (Chapter 3, Appendix II) are linked to the reception of the roman anglais in the context of the crisis of the roman à thèse, and the meditating influence of French criticism is revealed. The values of romance, adventure, and the common man (from Defoe to Stevenson, from Stevenson to Conrad) constitute the recurrent thread associated with the English tradition and with the Edwardian fictional canon, as these were mediated from France to Catalonia. This panorama of transmission enhances an understanding of Catalan views of the novel, in the light of Edwardian values (Chapter 4), as exemplified in Carles Riba's critical appraisal of two Catalan authors, in the appeal of Joseph Conrad's narrative technique and its influence on J.M. de Sagarra, as well as in the comparison of Frank Swinnerton's Nocturne (a best-seller of 1917) and its Catalan counterpart, M. Teresa Vernet's Les algues roges. This thesis also includes a chronology of the reception of Chesterton and a list of Catalan translations of English works of fiction.